Clinical manifestations of hereditary angioedema and a systematic review of treatment options. Issue 3 (3rd April 2021) - Rosi‐Schumacher, Mattie; Shah, Sejal J.; Craig, Timothy; Goyal, Neerav
Abstract: Objective: This study systematically reviews the existing literature on the management of hereditary angioedema (HAE) and provides an update on the clinical presentation and specific therapies. Methods: A literature search of PubMed and Embase databases was conducted from start of the database to February 2021. Inclusion criteria included relevant systematic reviews, randomized control clinical trials, prospective and retrospective cohort studies, and outcomes research published in English and available in full‐text. Out of 310 candidate articles, a total of 55 articles were included in our study. Results: The most common genetic form of HAE in up to 85% of cases is caused by low levels of C1 esterase inhibitor (C1‐INH) protein, leading to a bradykinin‐mediated increase in vascular permeability. During an attack of HAE, abortive treatment with C1‐INH replacement is most commonly described, however, icatibant, ecallantide, or fresh frozen plasma are also used. Long‐term prophylaxis in the form of C1‐INH replacement (subcutaneous or intravenous), monoclonal antibodies targeting plasma kallikrein, attenuated androgens, and transexemic acid should be considered for those who suffer from frequent, severe attacks. Conclusion: Progressively distal involvement of the upper airway, especially the larynx, has been shown to pose an increased risk of asphyxiation and death in the acute presentation of HAE. Evaluation by an otolaryngologist is often sought during the emergent clinical management of HAE; therefore, it is prudent that the consulting physician is well‐versed in the prompt recognition, triage of patients, and appropriate treatment modalities. Level of Evidence: 1A. Abstract :